An Albumin‐Photosensitizer Supramolecular Assembly with Type I ROS‐Induced Multifaceted Tumor Cell Deaths for Photodynamic Immunotherapy - Zhang, Jingtian; Jiao, Di; Qi, Xinwen; Zhang, Yufan; Liu, Xiaoang; Pan, Tengwu; Gao, Heqi; Liu, Zhaoyun; Ding, Dan; Feng, Guangxue (Advanced science, 2025)
Photodynamic therapy holds great potentials in cancer treatment, yet its effectiveness in hypoxic solid tumor is limited by the oxygen‐dependence and insufficient oxidative potential of conventional type II reactive oxygen species (ROS). Herein, the study reports a supramolecular photosensitizer, BSA@TPE‐BT‐SCT NPs, through encapsulating aggregation‐enhanced emission photosensitizer by bovine serum albumin (BSA) to significantly enhance ROS, particularly less oxygen‐dependent type I ROS for photodynamic immunotherapy. The abundant type I ROS generated by BSA@TPE‐BT‐SCT NPs induce multiple forms of programmed cell death, including apoptosis, pyroptosis, and ferroptosis. These multifaceted cell deaths synergistically facilitate the release of damage‐associated molecular patterns and antitumor cytokines, thereby provoking robust antitumor immunity. Both in vitro and in vivo experiments confirmed that BSA@TPE‐BT‐SCT NPs elicited the immunogenic cell death, enhance dendritic cell maturation, activate T cell, and reduce myeloid‐derived suppressor cells, leading to the inhibition of both primary and distant tumors. Additionally, BSA@TPE‐BT‐SCP NPs also exhibited excellent antitumor performance in a humanized mice model, evidenced by a reduction in senescent T cells among these activated T cells. The findings advance the development of robust type I photosensitizers and unveil the important role of type I ROS in enhancing multifaceted tumor cell deaths and antitumor immunogenicity. Supramolecular photosensitizers BSA@TPE‐BT‐SCT NPs are developed through encapsulating aggregation‐enhanced emission photosensitizer by bovine serum albumin (BSA) to boost type I reactive oxygen species generation for photoimmunotherapy. BSA@TPE‐BT‐SCT NPs induce multifaceted cell deaths, including apoptosis, pyroptosis, and ferroptosis, and these deaths synergistically facilitate the release of damage‐associated molecular patterns and antitumor cytokines, thereby provoking robust antitumor immunity.